Analisis Nilai Kerugian Akibat Deadstock Menggunakan Metode Net Present Value - . Sugiyatno; Aulia Fitriana (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
PT Bangun Jaya Alam Permai 1 (PT BJAP 1), a palm oil plantation company, has the largest central warehouse. There has been a buildup of inventory in the warehouse and eventually become deadstock due to improper company decision making. The purpose of this study was to determine losses due to deadstock with the concept of time value of money and the Net Present Value (NPV) method. The difference between the deadstock value between the past and the present is due to the influence of time value of money. Efforts can be made to minimize the losses by improving the planning decision-making system in terms of investment and other company policies.